Ferrous Sulfate-Iron (60 mg/d) Does Not Increase Risks to Malarial Infectivity, Pathogenic Bacterial Proliferation or Other Adverse Effects in Non-Anemic Healthy Adults. (29th May 2020) - Lewis, Erin; Chishti, Athar; Schwake, Christopher; Leong, John; Osburne, Marcia; Barger, Kathryn; Mason, Joel; Wu, Dayong; Meydani, Simin; Combs, Gerald
Abstract: Objectives: A double-blind, placebo-controlled, randomized clinical trial was conducted to determine the effects of different modalities of supplementation with ferrous sulfate (FeSO4 )-iron on the safety profiles of non-anemic, healthy adults. Methods: Eligible volunteers (194) were screened for general health; 108 were enrolled and randomized to four treatment groups (n = 27): a placebo (corn starch), daily doses of FeSO4 providing 60 mg Fe/d with or without a 15-component multiple micronutrient powder (UNICEF), or single weekly doses of FeSO4 providing 420 mg Fe. Treatment materials were provided in opaque capsules that were physically similar. The following safety profile indicators were assessed both before and after 28 days of intervention: infectivity of subjects' RBCs to Plasmodium falciparum determined ex vivo ; proliferation potential of 5 species of pathogenic bacteria ( Escherichia coli, Acinetobacter baumannii, Klebsiella pneumonia, Staphylococcus aureus, and Salmonella typhimurium ) in subjects' sera determined ex vivo; markers of inflammation (fecal calprotectin; serum myeloperoxidase, alpha-1 antitrypsin and TNFα); parameters of iron status (serum Fe, Hb, transferrin, % transferrin saturation, and ferritin). Adverse events were assessed by the study physician. Results: Results showed that no treatment affected: i) 28-day changes in either fasting or post-prandial levels of any parameter of Fe status; ii) 28-day changes in markers of gut or systemic inflammation; iii) RBC susceptibility to P. falciparum ; iv) ex vivo proliferation of and bacterial species except A. baumannii, for which the 28-day change in post-prandial peak growth rate index was less than that of the placebo treatment group; or v) subject reported adverse events, which were minimal. Conclusions: These results indicate that administration of FeSO4 in these modalities to non-anemic, healthy adults are well tolerated and do not increase their risks to malarial infection and bacterial proliferation. Funding Sources: The Bill and Melinda Gates Foundation U.S. Department of Agriculture – Agricultural Research Service (ARS), under Agreement No. #58–1950-4–003.